High‐Barrier, Biodegradable Food Packaging. Issue 10 (4th September 2018) - Habel, Christoph; Schöttle, Marius; Daab, Matthias; Eichstaedt, Natalie J.; Wagner, Daniel; Bakhshi, Hadi; Agarwal, Seema; Horn, Marcus A.; Breu, Josef
Abstract: Biodegradable, high‐barrier, flexible and transparent food packaging are required to replace current multilayered, metal‐ or halogen‐containing packaging that is nonrecyclable and nondegradable. An "all‐green" solution for food packaging made of a polylactic acid (PLA) foil (25 µm) furnished with a glycol chitosan‐clay nanocomposite coating (1.4 µm) is presented here that surpasses state‐of‐the‐art high‐performance materials like metallized poly(ethylene terephthalate) or poly(vinylidene chloride) even at harsh conditions (OTR = 0.17 cm 3 m −2 day −1 bar −1 at 75% relative humidity). While the barrier side of the foil inhibits bacterial colonization, the uncoated PLA side assures biodegradability. Such a Janus feature in combination with the superb barrier performance renders this waterborne bio‐nanocomposite coating a valuable alternative to conventional less eco‐friendly food packaging materials. Abstract : A transparent bio‐nanocomposite coating is applied via spray coating on a polylactic acid foil . The bio‐nanocomposite based on glycol chitosan and fluorohectorite exhibits oxygen transmission rates as low as 0.17 cm 3 m −2 day −1 bar −1 at elevated relative humidity of 75% and, thereby, is competitive to high‐performance packaging materials. Furthermore, the foils show inhibited microbial ( Pseudomonas fluorescence ) colonization of a potent biofilm former.